Examining the Impact of Disaster Experience with Winter Storm Uri and Climate Change Risk Perceptions on Support for Mitigation Policy - Ginger Orton; Laura Morgan Fischer; Cara Lawson (Journal of Applied Communications, 2023)
In February 2021, Winter Storm Uri swept across the central and eastern United States bringing extreme cold, widespread power outages, and rolling blackouts throughout Texas. This storm prompted climate change to emerge as a major topic of controversy and conversation with scientists and the public alike, and many began to think about the impacts of climate change. Risk communication experts have suggested prior disaster experience is a key mechanism of understanding how risk perceptions are shaped, and ultimately, on how individuals arrive at a judgment, evaluation, or attitude toward information and situations. Drawing from risk communication scholars, we examined the role of prior disaster experience, risk perceptions of climate change, and individual characteristics on its relationship with support for climate change mitigation policy. To do so, we sourced a Qualtrics public opinion panel of residents who lived in Texas during Winter Storm Uri (n = 486) to answer a series of questions related to prior disaster experience, their climate change risk perceptions, and their support of climate change mitigation policy. We conducted two hierarchical regression models to examine how prior disaster experience and climate change risk perceptions predicted support for policy. We found the inclusion of prior disaster experience provided a significant change in the respondents support for climate change mitigation policy. Although academic conversations in agricultural communications have started to explore the varying opinions of climate change, there is much more research needed in this area to fully explore the dynamic and complex phenomena of climate change.
Keywords: Disaster Experience; Risk Perceptions; Winter Storm Uri; Climate Change; Policy Support; Climate Change Mitigation